2000
DOI: 10.1128/iai.68.6.3776-3779.2000
|View full text |Cite
|
Sign up to set email alerts
|

The Collagen-Binding Adhesin Is a Virulence Factor in Staphylococcus aureus Keratitis

Abstract: A collagen-binding strain of Staphylococcus aureus produced suppurative inflammation in a rabbit model of soft contact lens-associated bacterial keratitis more often than its collagen-binding-negative isogenic mutant. Reintroduction of the cna gene on a multicopy plasmid into the mutant helped it regain its corneal adherence and infectivity. The topical application of a collagen-binding peptide before bacterial challenge decreased S. aureus adherence to deepithelialized corneas. These data suggest that the col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(90 citation statements)
references
References 17 publications
3
86
0
1
Order By: Relevance
“…aureus surface adhesins, collectively known as MSCRAMMS (microbial surface components recognizing adhesive matrix molecules), have also been recognized to mediate bacterial adherence to host extracellular matrix components, collagen, fibronectin, fibrinogen, laminin and elastin [80]. [161]; studied the role of MSCRAMM Cna (collagen-binding adhesin) in S. aureus keratitis and concluded that collagen-binding adhesin is a virulence factor for S. aureus keratitis and is involved in the early events of pathogenesis of S. aureus infection of the cornea. Similarly, [80] Likewise, Streptococci colonize different sites on human body by expressing multiple adhesins and hence their attachment to human tissues is mediated by a diverse group of bacterial surface proteins, MSCRAMMS [60].…”
Section: Adhesionmentioning
confidence: 99%
“…aureus surface adhesins, collectively known as MSCRAMMS (microbial surface components recognizing adhesive matrix molecules), have also been recognized to mediate bacterial adherence to host extracellular matrix components, collagen, fibronectin, fibrinogen, laminin and elastin [80]. [161]; studied the role of MSCRAMM Cna (collagen-binding adhesin) in S. aureus keratitis and concluded that collagen-binding adhesin is a virulence factor for S. aureus keratitis and is involved in the early events of pathogenesis of S. aureus infection of the cornea. Similarly, [80] Likewise, Streptococci colonize different sites on human body by expressing multiple adhesins and hence their attachment to human tissues is mediated by a diverse group of bacterial surface proteins, MSCRAMMS [60].…”
Section: Adhesionmentioning
confidence: 99%
“…cartilage (10). The results from several animal infection models suggest that Cnaexpressing S. aureus strains can induce and promote septic arthritis, endocarditis, keratitis, and osteomyelitis (22)(23)(24)(25)(26). Recently, a Cna homologue was detected in the animal pathogen Streptococcus equi (27).…”
Section: Streptococcus Pyogenes (Group a Streptococci (Gas)mentioning
confidence: 99%
“…Like most bacteria in the Cytophaga-Flavobacterium-Bacteroides complex, they have proteolytic properties, and identification of large numbers of cells in collagenous tissue also indicates collagenophilia. A collagenbinding adhesin was shown to be a virulence factor for some strains of Staphylococcus aureus causing keratitis in de-epithelialized corneas in a rabbit model (Rhem et al 2000). Whether a similar mechanism is important for the virulence of our bacterium is not known.…”
mentioning
confidence: 99%